Improving Ultra-Low Temperature Preservation Technologies of Soybean Pollen for Off-Season and Off-Site Hybridization - Jia, Hongchang; Liang, Xin; Zhang, Lixin; Zhang, Jinmei; Sapey, Enoch; Liu, Xianyuan; Sun, Yanhui; Sun, Shi; Yan, Hongrui; Lu, Wencheng; Han, Tianfu (Frontiers in Plant Science, 2022)
Preserving viable pollen is of great interest to breeders to maintain desirable germplasm for future in breeding. Ultra-low temperature preservation of pollen is an effective and safe way for long-term storage of plant germplasm resources. In this study, we improved methods for preservation of soybean pollen at ultra-low temperature. soybean flowers at initially-open stage were collected at 6-10 a.m. during the fully-bloom stage of soybean plants and were dehydrated for 10 h and then frozen and stored at -196 °C or -80 °C. In vitro culture experiments showed that the viability of preserved pollen remained as high as about 90%. The off-season (local site Heihe) and off-site (Beijing, after long-distance express delivery from Heihe) hybridization verification was conducted, and no significant difference in true hybrid rate was founded between the preserved pollen and the fresh pollen. The ultra-low temperature preservation technology for soybean pollen could break the spatiotemporal limit of soybean hybridization and facilitate the development of engineered soybean breeding.